Functional Effects of the Adams Procedure: A Retrospective Intervention Study - Kootstra, Thomas J. M.; van Doesburg, Margriet H.; Schuurman, Arnold H. (Journal of Wrist Surgery, 2018)
Background Injury to the distal radioulnar joint (DRUJ) causes swelling and ulnar-sided wrist pain. The Adams procedure stabilizes the DRUJ and shows promising short-term results.Purpose We studied the long-term functional outcome in patients who underwent the Adams procedure. We also tested the null hypothesis that there would be no difference in range of motion (ROM) and grip strength between the operated wrist compared to the unaffected side.Patients and Methods We identified 74 consecutive patients that were operated from March 2005 to February 2014. Twenty-three patients responded to our invitation and underwent clinical follow-up. Three patients had a re-do of the Adams procedure after presenting with postoperative DRUJ instability, one was excluded due to additional wrist surgery not related to the initial procedure. Wrist functionality in the remaining 22 patients was examined by measuring ROM in all planes and grip strength of the operated and non-operated hand. Functional outcome was measured by asking patients to complete the Disabilities of the Arm, Shoulder, and Hand (DASH) outcome measure and the Patient-Rated Wrist and Hand Evaluation (PRWHE).Results After a mean follow-up time of 5.0 years (standard deviation [SD] 2.0), we found that supination, pronation, and grip strength were significantly decreased in the operated wrist. Postoperative DASH and PRWHE-scores averaged 13.1 (SD 18.6) and 20.3 (SD 15.1), respectively.Conclusion The Adams procedure affects, but largely restores pronation and supination, and clinical examination, DASH, and PRWHE scores indicate that the Adams procedure leaves patients with upper extremity functionality comparable to a healthy population.Level of Evidence Level IV.
Keywords: function; long term; Adams procedure; DRUJ; reconstruction; DASH; PRWHE